Aroma Profile of Fruit Juice and Wine Prepared from Cavendish Banana (Musa Sp., Group AAA) Cv. Robusta - Ranjitha, K; Narayana, C K; Roy, T K (Journal of Horticultural Sciences, 2013)
A comparative study of the aroma profile of an alcoholic beverage (wine) and natural juice from banana cv. Robusta was performed. The study showed disappearance and synthesis of many aroma compounds during the fermentation process. Relative abundance of carbonyl compounds was high in the juice, and carboxylic acid content was higher in the wine. Aroma signature compounds of banana juice, isoamyl acetate, butyl isovalerate, isopentyl isovalerate, trans- 2- hexenal and butanoates were present only in a low proportion in the wine, while decanoic, dodecanoic and hexa decanoic acids (as well as their esters) were abundant in the banana wine. Synthesis compounds like methyl nonyl ketone, isoeuginol and 2-methoxy 4-vinyl phenol was greater during fermentation. Elemicin was present in high quantity in both the juice and the wine.